2019
DOI: 10.2478/joeb-2019-0012
|View full text |Cite
|
Sign up to set email alerts
|

Questioning the aloe vera plant and apple memristors

Abstract: Non-linear electrical properties of a (biological) tissue can be revealed by non-linear electrical measurements, which means that the applied stimulus itself affects the measurement. If resulting voltage–current plots exhibit pinched hysteresis loops, the underlying tissue may be classified as a memristor, a state dependent resistor. The aloe vera plant and apples have been found to be memristors. However, polarization processes on the electrodes are also non-linear and may affect the measurement. Apples and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…For example, it has been proposed that apples [8] and the aloe vera plant [9] are memristors. We demonstrated that similar results can be obtained from apples and apple juice and also from aloe vera and aloe vera extract and we concluded that the memristive properties actually originate from the change in polarization impedance [10].…”
Section: Introductionsupporting
confidence: 81%
“…For example, it has been proposed that apples [8] and the aloe vera plant [9] are memristors. We demonstrated that similar results can be obtained from apples and apple juice and also from aloe vera and aloe vera extract and we concluded that the memristive properties actually originate from the change in polarization impedance [10].…”
Section: Introductionsupporting
confidence: 81%
“…Similarly, electrodes interfacing with decellularized plant material could show pinched hysteresis, suggesting redox chemistry plays are marked role, counter to the claim that ion channels dominate within plant tissue. 147 Electrode material was not important for Physarum devices, 124,137,141,142,144 but the studies indicate that the higher voltages are potentially harmful to the organism, suggesting its responses are outside of the normal behavior for the species. Due to these systems being complex, it is likely that multiple factors contribute, such as combinations of ion channel-mediated currents and simple redox chemistry.…”
Section: Intact Biological Tissuementioning
confidence: 98%
“…In some cases, the measured i-v behaviors depended on the choice of electrode material. 123,128,131,134 Therefore, while electrochemical reactions with the electrode materials may have contributed, Volkov et al demonstrated that the memristor signatures strongly diminished or disappeared after treatment with potassium channel blockers. In the case of pumpkin seeds, germinated seeds show memristance, while dormant seeds do not.…”
Section: Review Of Bioderived Neuromorphic Architecturesmentioning
confidence: 99%
“…Memristors based on different materials like tantalum oxide [ 3 ], and zinc oxide [ 4 ] have been demonstrated, as well as, biological memristors like slime moulds [ 5 ] and apples [ 6 ], for example. However, in case of the apples the shown memristive properties may not origin from the apple itself but rather from chemical reactions on the electrodes [ 7 ].…”
Section: Introductionmentioning
confidence: 99%